High A + T content conserved in DNA sequences upstream of leuABCD in Escherichia coli and Salmonella typhimurium. - Haughn, G W (1986)
The nucleotide sequence of over 800 base pairs of DNA upstream of leuP was determined for Escherichia coli and Salmonella typhimurium. In both of these enteric bacteria, approximately 500 base pairs of A + T-rich sequences separates leuP from an upstream open reading frame. Although these A + T-rich sequences share little homology, the distribution of A + T base pairs within the region is strikingly conserved. Deletion of the A + T-rich sequences upstream of the E. coli leu operon does not markedly affect the strength of the leu promoter in vivo.